Pengaruh Metode Sas (Struktural Analitik Sintetik) Dalam Peningkatan Kemampuan Membaca Permulaan Siswa Kelas II Sekolah Dasar - Rukayah Rukayah; Abd Kadir; Sitti Jauhar (Universitas Negeri Makassar, 2022)
This study aims to find out the effect of the SAS Method on the ability to read Beginning of second grade students of SD Negeri 221 Pattiro Bajo, Sibulue District, Bone Regency. This type of research is an experimental one group pre-test-posttest design. Of the 19 populations taken as a whole as a sample. Data collection techniques used are tests, journals and observations. The data analysis technique used parametric tests which included descriptive statistical analysis, inferential. The early reading ability of second grade students at SD Negeri 221 Pattiro Bajo, Sibulue District, Bone Regency was still dominantly low (not fluent). This is evidenced by the results of the initial reading ability test before the experiment where only 6 out of 19 students 32 percent of students were declared quite fluent and complete with a score of 75. There was an increase in the initial reading ability of second grade students at SD Negeri 221 Pattiro Bajo, Bone Regency after the application of the SAS method in learning. This is evidenced by the results of the students' initial reading ability test after the treatment where the level of completeness increased to 89 percent from the previous only 32 percent. The SAS (Structural Analysis Synthetic) method has a significant effect on the early reading ability of second grade students at SD Negeri 221 Pattiro Bajo, Sibulue District, Bone Regency.